(untitled) (Applied Biological Research, 2015)
A field experiment was conducted at Research Farm, SKUAST Kashmir, Shalimar, Srinagar (India) to study the management of N through leaf colour chart (LCC) in two rice genotypes cv. ‘Jhelum’ and ‘SR-2’ during kharif 2012 and 2013. The soil of experimental field was silty clay loam with organic C 0.92%, pH 6.6, EC 0.22 dS m-1, available N 308.96 kg ha-1, P 33.38 kg ha-1 and K 169.26 kg ha-1. Genotype ‘SR-2’ gave significantly more yield than ‘Jhelum’ whereas LCC ≤ 5 @ 30 kg N ha-1 i.e. 150 kg N ha-1 applied in 5 splits gave significantly higher grain yield but was at par with 120 kg N ha-1 applied in 6 splits [LCC ≤ 5 @ 20 kg N ha-1] as compared to the recommended dose of 120 kg N ha-1. Chlorophyll content increased significantly with increase in N through The mean chlorophyll content varied from 0.22 to 0.39 and 0.22 to 0.40 g m-2 during 2012 and 2013, respectively. The correlation coefficient between SPAD and LCC, and SPAD and N were positively correlated at all growth stages of rice. Use of LCC also saved 10 to 40 kg N ha–1 over fixed-time N applications. The application of N through LCC ≤ 5 @ 30 kg N ha-1 gave higher gross returns, net returns and benefit cost ratio in both the rice genotypes.